INFLUENCE OF TIME MODES OF THERMAL TREATMENT ON Pt-Si SYSTEM MICROSTRUCTURE - V. A. Saladukha; V. A. Pilipenko; F. F. Komarov; V. A. Gorushko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The paper is purposed to establish the principles of the micro-structural changes of Pt-Si system during the rapid thermal treatment. The Pt films 43.7 nm thick were applied on the substrates of mono-crystal silicon KEF 0.5 with orientation (111) by means of the magnetron platinum target sputtering (purity of 99.95 %) on the unit MPC 603 with the cryogen pumping to the pressure of no less than 5∙10-5 Pa. Argon was used as a working medium, whose purity constituted 99.933 %. Rapid thermal treatment was performed in the mode of the thermal balance with irradiation of the reverse side of the wafer by means of the non-coherent light flow in the nitrogen medium within the temperature range from 200 to 550 °C with a step of 50 °С during 7 s. In parallel, the solid phase synthesis was performed of platinum silicide by means of the standard method with application of the continuous single stage thermal treatment in the analogue medium (T = 550 °C, t = 30 min). Temperature monitoring was performed by means of the thermal couple method with accuracy of ±0.5 °C. The grain size was determined by the translucent electron microscopy method. Thickness of platinum silicide under formation, its surface micro-relief and the separation boundaries with silicon were determined by means of the raster electron microscopy. It is demonstrated, that with the rise of the rapid thermal treatment one can observe growth of the platinum film on silicon. A comparative analysis was conducted of the average size of grains, micro-relief of the PtSi surface and its separation boundary with silicon for two methods of its formation with application of the rapid thermal treatment and with application of the traditional continuous thermal treatment at the temperature of 550 °C during 30 min in the nitrogen atmosphere. By means of the raster electron microscopy method it is demonstrated, that size of the micro-relief on the separation boundary of PtSi-Si does not exceed 15.9 nm and the size of grains is 37.7 nm. This is in 2.5 and 3.1 times smaller, then in the case of the traditional single stage continuous thermal treatment.